2022
DOI: 10.37950/ijd.v4i4.350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Social Assistance Programs During the COVID-19 Pandemic: Helping or Giving Addiction to the Public

Abstract: The emergence of a pandemic caused a lot of difficulties faced by the community to survive. This caused the government to intervene and provide various assistance to the community. However, there are often problems in the process of providing this assistance. This study aims to evaluate social assistance provided by the government to the community. This research will be conducted utilizing a qualitative methodology. This study utilized secondary data acquired from still-relevant research or previous investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The recent case of social assistance program during covid-19 pandemic have found that many individuals with sufficient financial ability, still apply for the program even though they have sufficient financial ability. These mindset are damaging to high quality human resources possibility if neglected (Haimah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The recent case of social assistance program during covid-19 pandemic have found that many individuals with sufficient financial ability, still apply for the program even though they have sufficient financial ability. These mindset are damaging to high quality human resources possibility if neglected (Haimah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%